The role of benchmarking in evaluating the performance of airports - a comparative analytical study between Iraqi airports, with a focus on Baghdad International Airport - أمل عبدالحسين كحيط (Iraqi Journal for Administrative Sciences, 2024)
This research aims to identify the role of benchmarking in assessing the performance of Iraqi airports ,this by taking advantage of others, stand on the strengths and weaknesses of them, and discrimination leading one in the field of air transport industry and the weak ones .The choice was to compare the performance of Iraqi airports among themselves with focus on the evaluation of the Baghdad international Airport, and through practical and analytical study and comparison of the performance of the Iraqi airports, depending on the performance indicators airports identified by the international civil Aviation Organization, and others related to civil aviation, the research found a range of results, including: benchmarking tool has a major role in assessing and improving the performance of enterprises generally, and airports especially, and by using some of the global performance criteria, , the research achieved a ranking to Iraqi airports ,especially to Baghdad international Airport and then identify the strengths or weaknesses to it.